MISSIOLOGI COSTMOTHEANDRIC RAIMON PANIKKAR - David Baluseda; Harefa, Febriaman Lalaziduhu (Jurnal Matetes STT Ebenhaezer, 2023)
Raimon Panikkar is a figure who pioneered cosmotheandricism, in which in his concept it is believed that there are three dimensions that cannot be separated but can be distinguished from Cosmos (world), Theos (God), and Antropos (human). In its development, cosmotheandric became a contemporary theology that was born from church doctrine and the truth recorded in the Bible. For Raimon Panikkar, the true concept of the trinity is moving from the paradigm of pericoresis. With regard to mission, cosmotheandric can be a contextualization tool in mission, even though in in-depth study, the purity of truth contained in the Bible is not in accordance with the doctrine taught or realized for ordinary people to understand God correctly. The research method used in researching the cosmotheandric concept is using descriptive methods and literature studies. The author hopes that with this scientific work it can be a reference in carrying out missions so that the paradigm used does not become wrong.